TEACHING FOREIGN LANGUAGES TO VISUALLY IMPAIRED CHILDREN - Oripova , Kamola Shuhrat qizi (Educational Research in Universal Sciences, 2023)
The majority of visually impaired persons have some degree of vision. However, there are those persons who have no sight at all. Some people have visual issues because of an eye ailment; others have visual problems because the neural pathways that carry information from the eyes to the brain are impaired; this is known as CVI (cerebral visual blindness). Blind or visually impaired children, like any children, can have a variety of linked difficulties such as specialized language impairments, childhood apraxia of speech, cleft palates, learning disorders, and intellectual disabilities. They may also suffer from hearing loss. They might have Down’s condition or another condition that is or is not connected with blindness. Blindness or visual impairment can be acquired such as a result of facial or head injuries from a car accident, or from a disease such as cancer of the eye or complications of diabetes. The majority of visually impaired persons have some degree of vision. However, there are those persons who have no sight at all. Vision provides information about nonverbal communication as well as meaning to words. Students with visual impairments require frequent hands-on encounters with real-world things, as well as auditory labels and descriptions and a rich reading environment (print and/or braille, depending on the student’s specific requirements). This article examines the theoretical elements of teaching strategies that may be used in the classroom to teach language learners with visual impairments and help them enhance their language abilities.